Study on the Effect of Electrochemical Dechlorination Reduction of Hexachlorobenzene Using Different Cathodes - Yingru Wang; Xiaohua Lu (Journal of Analytical Methods in Chemistry)
Hexachlorobenzene (HCB) is a persistent organic pollutant and poses great threat on ecosystem and human health. In order to investigate the degradation law of HCB, a RuO2/Ti material was used as the anode, meanwhile, zinc, stainless steel, graphite, and RuO2/Ti were used as the cathode, respectively. The gas chromatography (GC) was used to analyze the electrochemical products of HCB on different cathodes. The results showed that the cathode materials significantly affected the dechlorination efficiency of HCB, and the degradation of HCB was reductive dechlorination which occurred only on the cathode. During the reductive process, chlorine atoms were replaced one by one on various intermediates such as pentachlorobenzene, tetrachlorobenzene, and trichlorobenzene occurred; the trichlorobenzene was obtained when zinc was used as cathode. The rapid dechlorination of HCB suggested that the electrochemical method using zinc or stainless steel as cathode could be used for remediation of polychlorinated aromatic compounds in the environment. The dechlorination approach of HCB by stainless steel cathode could be proposed.